(untitled) (Scientific journal of the Fergana State University, 2024)
The distribution of electrons and holes in the Brillouin zone in semiconductors under the influence of electric and magnetic fields is briefly analyzed, with a focus on the distribution of electrons in the Brillouin zone as a result of the electric field effect.